PUERTO RICO AS ISLAND OF KNOWLEDGE: LESSONS LEARNED FROM SUCCESSFUL ENTREPRENEURS - Flores-Caraballo, Eliut Daniel (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2022)
Entrepreneurs from 10 different companies in the knowledge economy sector of Puerto Rico (PR), varying in operation from two to 25 years, were interviewed to understand which innovation ecosystem elements have contributed or hindered their companies’ growth. We learn about the journey of these companies and explore their leaders’ perception of how creating and operating a knowledge company in PR benefits or hampers their businesses. Entrepreneurs assess what could the commercial sector, educational institutions, and the government do to help their companies be more successful. They also reflect on the concept of Puerto Rico as an Island of Knowledge. Through the analysis of ten case studies, the article provides original and valuable insight into the entrepreneurial ecosystem in Puerto Rico to help researchers and policy makers understand the opportunities and pitfalls faced by Island-based innovators seeking to make their mark in the knowledge economy. We conclude that Puerto Rico is an Island of Knowledge in progress. The innovation ecosystem is currently growing but it remains smaller than needed to foster explosive growth. We found that entrepreneurship and company acceleration programs are having positive impact in growing the creation and sustainability of new knowledge companies on the Island. Puerto Rico is a good source of human capital for knowledge enterprises, but it could do better. Schools and universities need to teach entrepreneurship and bring more students to tech careers. Higher education curricula needs to be updated to cover a variety of new technologies and provide a myriad of practical skills and technical certifications to make graduates productive on day 1. Government and employers alike need to implement creative strategies to retain qualified talent on the Island.